Clinical characteristics and prognosis in patients with urosepsis from intensive care unit in Shanghai, China: a retrospective bi-centre study - Ying Sheng (BMC, 2021)
Abstract Background The purpose of this study was to retrospectively analyze clinical characteristics and prognostic risk factors of urosepsis patients admitted to two intensive care units in Shanghai, China. Methods Clinical data from patients diagnosed with urosepsis were retrospectively retrieved and analyzed from ICU in two regional medical centers from January 2015 to December 2019. Results Two hundred two patients were included in the subsequent analysis eventually, with an average age of 72.02 ± 9.66 years, 79.21% of the patients were female and the mortality rate of 15.84%.The proportion of patients with chronic underlying diseases such as diabetes and hypertension was relatively high (56.44, 49.50%, respectively), and the incidence of shock was also high (41.58%) correspondingly. The most common pathogen isolated was Escherichia coli (79.20%), of which the extended-spectrumβ-lactamases (ESBLs)(+) accounted for 42.57%. In multivariate analysis, the strongest predictors for death were mechanical ventilation (OR 7.260, 95% CI 2.200–23.963; P = 0.001),chronic kidney disease (CKD) (OR 5.140, 95% CI 1.596–16.550; P = 0.006), APACHE II score (OR 1.321, 95% CI 1.184–1.473; P < 0.001) and lactate (OR 1.258, 95% CI 1.037–1.527; P = 0.020). Both APACHE II score and lactate had the ideal predictive value, with the area under the ROC curve (AUC) of 0.858 and 0.805 respectively. Conclusion The patients with urosepsis were characterized by a higher proportion of female, older age, more percentage of comorbidities in this region, and patients with ESBLs (+) Escherichia coli infection were more prone to shock. Mechanical ventilation, comorbidity with CKD, APACHE II score and lactate were independent risk factors for death in urosepsis patient, but lactate level and APACHE II score had better predictive value for prognosis.